Trend Analysis to Analyze Performance Assessment of Pt Unilever Indonesia Tbk in 2019 – 2021 - Salmaa Alya Audy Rachmani Sutisna; Hari Sulistiyo (Universitas Islam Lamongan, 2022)
Research was conducted to determine the performance of PT Unilever Indonesia Tbk based on the results of financial statements and also income statements with the use of trend analysis. By using analytical techniques, descriptively using a quantitative approach which is financial statement data and income statements that are analyzed so that they can get information related to how financial performance in Unilever Indonesia companies based on financial statements and also income statements. Unilever's company experienced some increases in 2020, but in 2021 it experienced a decline due to the pandemic. But the company kept going despite the decline.